Study of SiNWs / hybrid solar cell - Zhang, Siyuan (2015)
The conventional approaches to generate energy have caused serious energy crisis and climate changes due to the pollution coming along with it. There is a strong demand to seek renewable and environmentally friendly energy sources. Solar energy is a potential candidate because of its abundance and cleanliness. Intensive research has been conducted to develop various approaches to improve the efficiency and lower the cost of solar cells that are used to harness solar energy. For example, nanostructure has been intensively investigated for light trapping to improve the device performance and has been applied to increase the cell efficiency. In this report, a new type of silicon nanowire hybrid solar cell based on Si and PEDOT:PSS will be introduced. The whole report will be divided into two parts. The first part presents the basic knowledge of solar cell including the working principle, development history of silicon nanowire hybrid solar cell. Following that, the basis of silicon nanowire will be introduced. The second part of this report focuses on the fabrication process of the solar cells and their characterization. The effects of length of nanowire and the passivation treatment on the cell performance will be discussed and analyzed in detail.